2012
DOI: 10.1108/14777831211232236
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine nurseries for marine fish

Abstract: Access to this document was granted through an Emerald subscription provided by UNIVERSITY OF GUELPH For Authors:If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service. Information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comWith over forty years' experience, Emerald Group Publishing is a lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 120 publications
(199 reference statements)
0
6
0
2
Order By: Relevance
“…According to Elliott (2002), climate change has the potential to affect major aspects of fish physiology, such as their salinity and temperature tolerances; this effect influences their ability to occupy estuarine habitats and ultimately the larger-scale distribution of species. Temperature-dependent processes vary over a species' latitudinal distribution, such that fish populations living at the edge of their species range may be more influenced by changes in temperatures than those living at the centre of their range (Martinho et al 2012). Distributions of these edge populations can be expected to shift as environmental conditions change.…”
Section: Temperaturementioning
confidence: 99%
“…According to Elliott (2002), climate change has the potential to affect major aspects of fish physiology, such as their salinity and temperature tolerances; this effect influences their ability to occupy estuarine habitats and ultimately the larger-scale distribution of species. Temperature-dependent processes vary over a species' latitudinal distribution, such that fish populations living at the edge of their species range may be more influenced by changes in temperatures than those living at the centre of their range (Martinho et al 2012). Distributions of these edge populations can be expected to shift as environmental conditions change.…”
Section: Temperaturementioning
confidence: 99%
“…Previous studies from the last decade (from 2003 onwards) have already highlighted the importance of the estuary for maintaining marine species coastal stocks, such as D. labrax, S. solea and P. flesus Dolbeth et al, 2008;Vasconcelos et al, 2008). Still, there was slight decrease in the total percentage of commercial species during the drought period, as also debated by Dolbeth et al (2008), which might be related to recruitment variability in marine fish associated to freshwater flow or to higher predation pressure Martinho et al, 2012).…”
Section: Commercial Importancementioning
confidence: 99%
“…The abundance of fish is highly variable through time and the species occurring at the adult stage in estuaries do not necessarily reflect the species composition at the larval stage (Amorim et al, 2018; Martinho et al, 2012; Primo et al, 2013). Early stages often spend months to years in these environments before recruiting to coastal adult populations (see reviews by Able, 2005; Beck et al, 2001; Gillanders et al, 2003), as observed for the Atlantic menhaden ( Brevoortia tyrannus , Clupeidae; Kroger & Guthrie, 1973), the common sole (Koutsikopoulos et al, 1995) or the European flounder ( Platichthys flesus , Pleuronectidae; Kerstan, 1991).…”
Section: Which Fish Species Visits Estuaries? Contrasting Life Histor...mentioning
confidence: 99%